Teacher’s Roles in Implementing Multiple Intelligences in Inclusive English Education: A Case Study of a Kindergarten in Ende Regency - Hadun, Leonarda Noventalia Tude; Pratiwi, Widya Rizky; Sujiatmoko, Ahmad Heki (CV. Tripe Konsultan, 2026)
This study is grounded in the need to address diverse learning needs in inclusive kindergarten English classrooms through the Multiple Intelligences framework. Drawing on inclusive education principles and the Kurikulum Merdeka enriched with the Nazareth Global Education curriculum, the research explores Multiple Intelligences based instructional practices, challenges faced by teachers, and perceived effects on students’ motivation and English learning outcomes at Nazareth School.This qualitative case study examines the implementation of the Multiple Intelligences approach in inclusive English learning at a kindergarten in Ende Regency. Data were collected through interviews, classroom observations, and document analysis to explore instructional strategies, implementation challenges, and teachers’ perceptions of students’ motivation and learning outcomes, providing in-depth insights into inclusive English teaching practices in early childhood education.This study reveals that the Multiple Intelligences approach effectively supports inclusive English learning for kindergarten students at Nazareth School. Through multimodal instruction, digital platforms, and flexible learning environments, Multiple Intelligences enhances students’ motivation, engagement, linguistic development, and social interaction. Despite challenges in activity design, classroom management, and time constraints, Multiple Intelligences fosters holistic learning outcomes in early childhood education.This study concludes that the Multiple Intelligences approach effectively supports inclusive English learning at Nazareth School through structured, multimodal, and collaborative instructional practices. Despite challenges in activity design, classroom management, and preparation, Multiple Intelligences enhances students’ motivation, engagement, linguistic development, and holistic growth. The study offers practical recommendations for teachers, schools, parents, policymakers, and future research.